Functional analysis of conserved C. elegans bHLH family members uncovers lifespan control by a peptidergic hub neuron. - G Robert Aguilar; Berta Vidal; Hongzhu Ji; Joke Evenblij; Chien-Po Liao; Hongfei Ji; Giulio Valperga; Christopher Fang-Yen; Oliver Hobert (PLoS Biology)
Throughout the animal kingdom, several members of the basic helix-loop-helix (bHLH) family act as proneural genes during early steps of nervous system development. Roles of bHLH genes in specifying terminal differentiation of postmitotic neurons have been less extensively studied. We analyze here the function of 5 Caenorhabditis elegans bHLH genes, falling into 3 phylogenetically conserved subfamilies, which are continuously expressed in a very small number of postmitotic neurons in the central nervous system. We show (a) that 2 orthologs of the vertebrate bHLHe22/e23 genes, called hlh-17 and hlh-32, function redundantly to specify the identity of a single head interneuron class (AUA), as well as an individual motor neuron (VB2); (b) that the PTF1a ortholog hlh-13 acts as a terminal selector to control terminal differentiation and function of the sole octopaminergic neuron class in C. elegans, RIC; and (c) that the NHLH1/2 ortholog hlh-15 controls terminal differentiation and function of the peptidergic AVK head interneuron class, a known neuropeptidergic signaling hub in the animal. Strikingly, through null mutant analysis and cell-specific rescue experiments, we find that loss of hlh-15/NHLH in the peptidergic AVK neurons and the resulting abrogation of neuropeptide secretion from these neurons causes a substantially extended lifespan of the animal, which we propose to be akin to hypothalamic control of lifespan in vertebrates. Our functional analysis reveals themes of bHLH gene function during terminal differentiation that are complementary to the earlier lineage specification roles of other bHLH family members. However, such late functions are much more sparsely employed by members of the bHLH transcription factor family, compared to the function of the much more broadly employed homeodomain transcription factor family.